Morphology and disaccharidase activity of small intes- tinal mucosa in post-weaning-induced malnourished rats and after realimentation - Rustadi Sosrosumihardjo; Agus Firmansyah; Asri Rasad; Daldiyono Harjodisastro; Endi Ridwan; Septilia Inawati Wanandi; Dwirini Retno (Paediatrica Indonesiana, 2006)
Background The most common cause of failure to thrive in in-fants is malnutrition which causes histological and biochemicalchanges of small intestine. Studies on histology and enzyme ac-tivity of small intestinal mucosa were not much developed.Objective To study about histology and disaccharidases activity ofsmall intestinal mucosa in post-weaning-induced malnourished rats.Methods We used Sprague-Dawley white rats as the subjects ofthis study with post test-control group design. The study was per-formed at the CentER for Research of Food and Nutrition Devel-opment from April 2003 to December 2004.Results There were a decrease of body weight (hypotrophy nor-moblastic) and an increase of disaccharidase activity of small in-testinal mucosa in post-weaning-induced malnourished rats. Afterrealimentation, there were an increase of body weight, an improve-ment of the hypotrophy, and a decrease of the enzyme but theystill cannot reach normal condition.Conclusion In malnourished rats, there are decrease of bodyweight hypotrophy normoblastic and increase of disaccharidasesactivity of intestinal mucosa that are improved after realimentation